Representasi Konsep Diri (Self Concept) dalam Lirik Lagu “Mengenal Lebih Jauh” Karya Nuca : Analisis Semiotik Ferdinand De Saussure - Aisyah Salwa Salsabila (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Music and song lyrics serve as a means of self-expression capable of conveying messages, feelings, and representing a person's self-concept in the face of reality and social expectations. This research focuses on a semiotic analysis of the lyrics of the song "Mengenal Lebih Jauh" by Nuca to identify the representation of self-concept and individual understanding of themselves amidst complex social demands. This research aims to reveal an analysis of self-concept representation in the lyrics of the song "Mengenal Lebih Jauh" by Nuca. Using Ferdinand de Saussure's semiotic analysis approach, the researcher attempts to uncover the meaning within the lyrics of the song "Mengenal Lebih Jauh." The results of this study reveal that the lyrics of the song "Mengenal Lebih Jauh" by Nuca contain a relationship between the signified and the signifier. The lyrics of this song are not just a beautiful sequence of words, but also a form of communication that expresses very human feelings and emotional experiences. The lyrics from the first to the sixth stanzas are a series of stories that depict a person's journey in understanding themselves and others.